The Impact of Internships on Recruiting and Retaining Mental Health Workers: Views From Students and Their Supervisors. (3rd July 2019) - Slaughter, Jamel; Hoefer, Richard
ABSTRACT: In 2015, 81% of counties in Texas were designated as full or partial Mental Health Professional Shortage Areas. To address this problem, we worked with a community-based association of mental health practitioners, using the social theory of career selection, to explore factors that influence students to join the mental health field. Our goal was to better understand how to recruit and retain mental health-trained students. We interviewed bachelor and master-level mental health interns in social work, counseling, and psychiatric nursing and field instructors using semistructured, open-ended interviews. Five themes emerged from the interviews: 1) attraction to mental health; 2) professional experience; 3) impact capacity; 4) develop social work skills; and 5) intern preparedness.